Isolation of Bacillus spp. from the rhizosphere of olive trees planted in Castelar - Rossi, Maria Sol; Jones, Leandro; Otero, Maria Laura; Roca, Mónica; Matias, Angel Cesar; Perez, Beatriz Alida (ASAHO, 2024)
Drechslera, Fasarium Verticillum are important soilborne pahogen, causing losses in a wide variety of important crop (Tijamos et. al., 1997). Alternative to chemical control are antagonistic microorganisms (Weller, 1988). The rhizhosphere is defined as a the layer of soil influenced by root metabolism, In comparison to root - free soils, the rhizhosphere forms a nutrient rich niche for microorganisms as a result of exudationof compounds Lorenz Hiltner, 1904).